Penelitian semasa status penilaian impak sosial di Sabah - Gaim James Lunkapis; Justin Sentian (Universiti Malaysia Sabah, 2013)
This research critically assesses the quality of Social I mpact Assessment which normally presented as a chapter in the Environmental Impact Assessment reports. The need for Social Impact Assessment in Malaysia has been acknowledged by the Dasar Sosial Negara as a tool to assess the implementation of projects. programs and policies. Consequently, this follow-up research was necessary in order to understand and to assess the practical implementation of this tool. The objectives therefore were to find out the gaps in the implementation process. This was made possible through access to Environmental Impact Assessment reports from the Sabah Environment Protection Department starting from year 2000 to 2010. Assessment methods utilized Delphi Technique and Goal Achievement Matrix to evaluate the quality of this chapter in each of the report examined. Field studies and series of workshops were necessary to gauge feedback from agencies which were useful to frame the final outputs. Outcomes from this research was useful to chart the future undertaking of Social Impact Assessment activities in the state of Sabah which could improve the quality, trustworthiness and efficiencies of this chapter of Environmental Impact Assessment reports.